A boundary value problem for higher-order semilinear partial differential equations. Issue 5 (4th May 2019) - Kharibegashvili, S.; Midodashvili, B.
ABSTRACT: One boundary value problem for a class of higher-order semilinear partial differential equations is considered. Theorems on existence, uniqueness and nonexistence of solutions of this problem are proved.